2022
DOI: 10.1111/joa.13723
|View full text |Cite
|
Sign up to set email alerts
|

The diverse terminology of reptile eggshell microstructure and its effect on phylogenetic comparative analyses

Abstract: Reptile eggshell ensures water and gas exchange during incubation and plays a key role in reproductive success. The diversity of reptilian incubation and life history strategies has led to many clade-specific structural adaptations of their eggshell, which have been studied in extant taxa (i.e. birds, crocodilians, turtles, and lepidosaurs). Most studies on non-avian eggshells were performed over 30 years ago and categorized reptile eggshells into two main types: "hard" and "soft" -sometimes with a third inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 342 publications
1
13
0
Order By: Relevance
“…This Upper Cretaceous egg was found in a marine deposit and was associated with an ammonite ( Baculites ) fossil (Fukuda & Obata, 1991). Because all known sea turtles lay ‘soft’ eggs (but see Legendre et al, 2022 for a critical appraisal of the ‘soft’ and ‘hard’ dichotomy), which are rarely fossilized (Hirsch, 1996; Legendre et al, 2020), Fukuda and Obata (1991) inferred that the ‘hard’ egg does not belong to sea turtles and was allochthonously transported to the marine deposit. However, Cadena et al (2019) confirmed that protostegid marine turtles laid ‘hard’ eggs unlike ‘soft’ eggs of modern sea turtles.…”
Section: Discussionmentioning
confidence: 99%
“…This Upper Cretaceous egg was found in a marine deposit and was associated with an ammonite ( Baculites ) fossil (Fukuda & Obata, 1991). Because all known sea turtles lay ‘soft’ eggs (but see Legendre et al, 2022 for a critical appraisal of the ‘soft’ and ‘hard’ dichotomy), which are rarely fossilized (Hirsch, 1996; Legendre et al, 2020), Fukuda and Obata (1991) inferred that the ‘hard’ egg does not belong to sea turtles and was allochthonously transported to the marine deposit. However, Cadena et al (2019) confirmed that protostegid marine turtles laid ‘hard’ eggs unlike ‘soft’ eggs of modern sea turtles.…”
Section: Discussionmentioning
confidence: 99%
“…Other than two lineages of geckos with hard shells, oviparous squamates have parchment-shelled eggs with a thin layer of calcium deposits on the outer surface of the shell membrane (Blackburn & Stewart, 2021;Choi et al, 2018). Monotremes have an eggshell but far less has been documented about its structure compared to other amniotes (Legendre et al, 2022). The structure and physiological mechanisms involved with eggshell calcification are most well resolved in birds (Choi et al, 2018;Francesch et al, 1997;Jonchere et al, 2010Jonchere et al, , 2012Mikšík et al, 2010;Rose-Martel, Du, & Hincke, 2012).…”
Section: Eggshell Depositionmentioning
confidence: 99%
“…In birds, the organic components of uterine fluid promote the formation of calcite (Hernández-Hernández, Gomez-Morales et al, 2008;Hernández-Hernández, Rodriguez, et al, 2008;. Most amniotes use this polymorph (Hernández-Hernández, Gomez- Hernández-Hernández, Rodriguez, et al, 2008;Legendre et al, 2022;.…”
Section: ) Mineral Composition Of Eggshellsmentioning
confidence: 99%
See 2 more Smart Citations